Brand authenticity's influence on brand loyalty: an examination of the mediating role of perceived value and brand trust in Wardah halal cosmetics - Suci Aprilia Hendri; Abror Abror (Marketing Management Studies, 2023)
The purpose of this study was conducted to analyze the effect of brand authenticity as seen from brand individuality, brand consistency, and brand continuity on brand loyalty which is mediated by perceived value and brand trust in the Wardah halal cosmetics brand. The structural equation modeling used is smartpls 4.0 software to analyze 200 respondents who use the Wardah halal cosmetic brand within the last three months and have made repeat purchases with data collection techniques using quentionnaire distribution. The research findings show that : (1) brand authenticity has a significant effect on perceived value (2) brand authenticity has a significant effect on brand trust and (3) brand authenticity has a significant effect on brand loyalty. Furthermore,the (4) perceived value of the wardah halal cosmetic brand also have a significant effect on brand loyalty and (5) brand trust of the wardah halal cosmetic brand also have a significant effect on brand loyalty. And (6) brand authenticity on the wardah cosmetic brand which is mediated by perceived value has a significant effect on brand loyalty. and (7) brand authenticity on the wardah cosmetic brand which is mediated by brand trust also has a significant effect on brand loyalty. This study suggests that companies can maintain and improve brand authenticity of their brands by conducting massive promotions on every new product launched so that the price is easily accessible to various groups son that Wardah cosmetics can be recognized by its users to get brand loyalty.